Kontektualisasi Risalah al-Qadha Masa Khalifah Umar Bin Khattab dan Relevansinya Terhadap Peradilan Agama di Indonesia - Bahrul Ulum; Ibnu Alfin (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
History proves that the judiciary has existed and been known since time immemorial, in the course of Islamic history, the judicial system has been known since the time of the Prophet Muhammad. In this Treatise there is a lot of legal content and things that we can learn and apply, in the Religious Courts in Indonesia there are many similarities and conformities with the Treatise of Umar which was given to Abu Musa Al-Asy Ari, in fact many scholars quote this Treatise, because when studied in more depth this Treatise can really be used as a legal benchmark and guide to apply, as well as many judges in Indonesia who study and apply it when deciding legal and justice cases. The aim is to find out the extent of the Al-Qadha Treatise and its relevance in Religious Courts when applied from the perspective of one of the books: Religious Court Procedural Law Plus Principles of Islamic Procedural Law in Umar Bin Khattab's Qadha Treatise. This research method is in the library research genre with the aim of researchers being able to find out that the Al-Qadha Treatise is very relevant to Religious Courts in Indonesia, using a qualitative descriptive analysis approach. The results of this research show that Umar Bin Khattab sent a letter to judge Kuffah. In the contents of the letter there are two legal provisions; firstly the procedures of religious courts, secondly the competence of judges. b) During Umar's leadership the system of power was divided into the three parts that we know today (trias politica). c) The concepts in the Al-Qadha Treatise are similar to the Religious Courts in Indonesia. d) Likewise, in his ijtihad, Umar Bin Khattab cannot be separated from the Al-Quran, Ijma, Qiyas and Ra'yu. e) Indonesian Islamic Courts, several points in Umar's letter are in line with Indonesian Court procedures, this indicates that, in fact, the judiciary during the time of Umar Bin Khattab was an Islamic Court, which also applies to Islamic Courts in Indonesia.